Acquired Horner's syndrome in an infant: A case report - Sumana J Kamath; Madhurima A Nayak; Flora D Lobo (Wolters Kluwer Medknow Publications, 2014)
Horner's syndrome has varied etiology. We report a case of acquired Horner's syndrome in an infant. A 3-month-old female child was referred for drooping of right eye upper lid on the second postoperative day following neck surgery. On examination, she had mild ptosis of right eye; with enophthalmos and miosis. A clinical diagnosis of Horner's syndrome was made. One percent phenylephrine test was done which dilated right pupil, suggestive of a postganglionic lesion. The sample was biopsied and revealed an infected lymphatic cyst. Horner's syndrome is a collection of signs due to interruption of sympathetic innervation to eye and face, characterized by miosis, mild ptosis, enophthalmos, and anhydrosis. The sympathetic pathway is a three neuron pathway. The present lesion is in the third order fibers which form plexus around the internal carotid artery. Dissection along the carotid can be an important cause for interruption of the sympathetic pathway.